Full-scale electric vehicles penetration in the Danish Island of Bornholm—Optimal scheduling and battery degradation under driving constraints. (June 2019) - González-Garrido, Amaia; Thingvad, Andreas; Gaztañaga, Haizea; Marinelli, Mattia
Highlights: Characterization of the population driving behaviour based on transport statistics. Modelling of the aggregate plugin behaviour based on usage data from 10.000 EVs. Economic analysis of the value of smart charging, considering prices and taxes in Denmark. Analysis of the consequences in term of battery degradation considering EV usage. Abstract: The paper proposes an analysis of a 100% electric vehicle (EV) scenario on the energy system of the island of Bornholm in Denmark. The paper intends to present challenges and opportunities that a realistic system would face when completely shifting to electric transportation. The EVs are subject to different charging strategies in order to assess the impact on the grid, the potential savings on the charging cost and the effects on battery degradation. In contrast to uncontrolled charging, smart charging strategies are designed not only to satisfy the same charging requirements at the EV departure time, but also maximize the savings on the charging cost and avoid interconnection congestions. Smart strategies bring a reduction in annual charging cost around 12%, on top of a reduction in the degradation because of lower average SOC and number of cycles. Moreover, results show a limited benefit in bidirectional charging because of a marginal increase in savings: this more demanding operation, which allows discharges, leads to higher battery degradation, due to the increase in the number of cycles.